PERAN KEPALA SEKOLAH SEBAGAI MANAJER DALAM MENINGKATKAN MUTU AKADEMIK DI SEKOLAH DASAR NASIMA KOTA SEMARANG - Siti Rochajati; Muhdi; Noor Miyono (STKIP Subang, 2023)
The school principal has a strategic role in utilizing the school. School principals are required to have the ability to manage and develop school organizations, in order to improve the school's academic quality. Focus of the research is to describe and analyze the role of the principal as a manager in improving academic quality at Nasima Elementary School, Semarang City. The research approach used is qualitative. This type of research is a case study. Qualitative research design through data condensation, presenting data (data display), and drawing conclusions or verification (conclusion drawing and verification). Data collection techniques are interviews, observation and documentation. This research uses triangulation of sources and methods. Data analysis in three steps: data reduction, presenting data, and drawing conclusions. The research results show that: 1) The role of the school principal as a manager in planning is carried out using planning procedures including identification of needs, school programs, school program priorities, and school program socialization. 2) the role of the school principal as a manager in organizing is carried out by organizing procedures including the placement of school resources, organizational development, assignment and delegation of authority. 3) the role of the principal as a manager in mobilization is carried out by the principal, including directing the principal and motivating the principal. 4) the role of the principal as a manager in supervision carried out by the principal includes making assessments, evaluating implementation activities, and following up. The author suggests that school principals pay more attention to planning and organizing. mobilization and surveillance. Teachers are required to always be ready to carry out activities.